Resistance Test of Bacterial Causes of Urinary Tract Infection Against Ciprofloxacin and Ceftriaxone Antibiotics - Zamharira Muslim; Aisyah Novrianti; Dira Irnameria (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
Urinary Tract Infection (UTI) is an infection caused by bacteria in the urinary tract. UTI is the second infectious disease after respiratory infections with the highest number of cases of 8.3 million each year. The main therapy for UTIs is the use of antibiotics. However, at present there are many incidents of antibiotic resistance. This study aims to determine the sensitivity of antibiotics to bacteria that cause urinary tract infections. Sampling was taken using accidental sampling method and willing to fit the research context. The antibiotics tested were Ciprofloxacin and Ceftriaxone. The number of samples in this study was 18 samples with the finding of 15 Gram positive and 3 Gram negative samples after Gram staining. The results of the examination of the inhibition zone diameter of the ciprofloxacin antibiotic were mostly resistance (72.2%), a small proportion of intermediates (5.6%), and a small proportion were still sensitive (22.2%). Ceftriaxone antibiotic almost all (77.8%) resistance, a small proportion (5.6%) intermediates, a small proportion (16.7%) sensitive to urinary tract infections. From these results it can be concluded that the inhibition zone diameter of ciprofloxacin and ceftriaxone antibiotics is mostly resistant, so it is less effective for use in the treatment of urinary tract infections.